# Solve by Addition/Elimination 2a+3b=6 and 5a+2b-4=0

**Solution:**

Given 2a+3b=6 and 5a+2b-4=0

Let 2a+3b=6 be eq(a)

And

5a+2b-4=0 be eq(b)

In order to perform addition by elimination method, we need to make the coefficient the same of either “a” or “b” variables.

Hence, multiply equation (a) with “5” , we get

10a+15b +30 =0 ……………………..(a’)

Multiply equation (b) with “2”, we get

10a+4b- 8 =0 …………………….(b’)

Now, add eq(a’) and eq(b’) We get

11b =22

⇒ b=2

Put b=2 in eq(a), we get

2a+3b =6

⇒ 2a+3(2) =6

⇒ 2a =6-6

⇒ a=0

## Solve by Addition/Elimination 2a+3b=6 and 5a+2b-4=0

**Summary: **

By Addition/Elimination 2a+3b=6 and 5a+2b-4=0, we get a=0 and b=2.